2020
DOI: 10.7203/rase.13.1.16042
|View full text |Cite
|
Sign up to set email alerts
|

La influencia del género en el aprendizaje matemático en España. Evidencias desde PISA

Abstract: Diferentes estudios muestran que la variable sexo incide en el rendimiento matemático del alumnado (Rodríguez, Delgado y Bakieva, 2011; Rodríguez-Mantilla, Fernández-Diaz y Jover, 2018). El presente trabajo indaga sobre la existencia y evolución de una brecha de género en el aprendizaje de las matemáticas en España, en base a los resultados de la evaluación PISA (Programme for International Student Assessment) en todas sus ediciones. Se valora también la competencia matemática del alumnado español sin diferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…However, as we have already indicated, it seems that a gender gap continues to exist at least in high performers (in some countries), despite the fact that the evidence points to its progressive reduction. And in the specific case of Spain, which we analyze in this paper, Fuentes De Frutos and Renobell Santaren (2020) concluded that the gender gap (in general terms, not only among high performers) not only exists but has even increased.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, as we have already indicated, it seems that a gender gap continues to exist at least in high performers (in some countries), despite the fact that the evidence points to its progressive reduction. And in the specific case of Spain, which we analyze in this paper, Fuentes De Frutos and Renobell Santaren (2020) concluded that the gender gap (in general terms, not only among high performers) not only exists but has even increased.…”
Section: Introductionmentioning
confidence: 76%
“…However, there still seems to be a gender gap when it comes to mathematics achievement. Fuentes De Frutos and Renobell Santaren (2020, p. 72) concluded that “[Spanish male students present better scores in mathematics [six PISA editions, from 2000 to 2015] than female students in percentages that vary depending on the edition. The gender gap detected is stable and has even increased during the last editions with respect to the previous ones.” In fact, the results of TIMSS (Trends in International Mathematics and Science Study) also show higher performance in mathematics in boys in Spain, both in primary and secondary education (UNESCO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that there is a large, worldwide sample for the PISA tests means that the conclusions are extremely important in the development of education policy. Its conceptual framework has been used in many studies (García-Perales, 2014;Ferreira et al, 2017;Rodríguez-Mantilla et al, 2018;Fuentes and Renobell, 2019;Sason et al, 2020). The distinctive characteristics of PISA include (Ministerio de Educación y Formación Profesional, 2019): seeking to guide educational policies, integration of the concept of competence in assessment, the important role of autonomous and lifelong learning, regular deployment, and sensitive international coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many conclusions from PISA relating to mathematics, reports have stressed that students' interest in and enjoyment of this area is low, and even noted the presence of personal issues such as anxiety and lack of confidence, especially in girls (Organization for Economic Cooperation, and Development, 2013;Mizala et al, 2015;Organization for Economic Cooperation and Development, 2019d). Throughout the PISA assessments, boys have always had better results than girls in mathematical competence (Ministerio de Educación y Formación Profesional, 2019), with sex being a predictor variable of mathematical performance (Farfán and Simón, 2017;Fuentes and Renobell, 2019;Palomares-Ruiz and García-Perales, 2020). Biological and social factors may act in an interrelated way (Chamorro-Premuzic et al, 2009;Muelas, 2014), including intellectual capacity (Schillinger et al, 2018), complex mathematical reasoning (Desco et al, 2011) and other factors of an individual nature with an impact on the mathematical learning process (Song et al, 2010;Marsh and Martin, 2011;Rodríguez and Guzmán, 2018), school (Carey et al, 2016;Dowker et al, 2016;Schillinger et al, 2018), and family (Pelegrina et al, 2002;Ferreira et al, 2017;Rodríguez-Mantilla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the targets proposed for this goal is to ensure the effective participation of women in all contexts, facilitating their leadership, decision-making, and empowerment at all levels. Despite this, there are still some problems regarding full parity [33][34][35]; a clear example being the existing inequality in scientific disciplines between men and women in different domains, as indicated by various studies [36][37][38][39][40], including mathematics [41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%